Effect of Sodium Chloride and Ethanol on Autolysis of Spent Baker’s Yeast Generated from Sago Bioethanol - Nur Hidayah, Pawaja (Universiti Malaysia Sarawak, (UNIMAS), 2022)
iv ABSTRACT Spent Baker’s yeast are generated as a by-product from brewery and bioethanol industries. The excessive production of this waste may lead to an increment in environmental pollution. Since spent yeast contains several useful components, it will be wise to convert it into valuable products such as via autolysis process. Sodium chloride and ethanol are known as great plasmolysing agents to enhance any cell lytic process. The combination use of ethanol and sodium chloride in the autolysis of spent Baker’s yeast, especially those generated from sago bioethanol has received little attention in the literature. Hence, this research is conducted to investigate the effect of sodium chloride and ethanol on autolysis of spent Baker’s yeast generated from sago bioethanol. The spent Baker’s yeast was autolysed with using three different settings which are 5% sodium chloride, 5% sodium chloride with 5% ethanol, and 5% ethanol. The amount of protein and carbohydrate released in the autolysates were determined using lowry assay and phenol-sulphuric acid method, respectively. The results showed that the autolysis treated with 5% sodium chloride shows the highest production of protein and carbohydrate released which were 8.3-fold and 4.7-fold higher compared to the control experiment. In general, this work gives useful insight into valorisation of spent Baker’s yeast generated from sago bioethanol.